1979
DOI: 10.1159/000237856
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of Pretazettine, a Narcissus Alkaloid, on Spontaneous AKR Leukemia

Abstract: A narcissus alkaloid, pretazettine hydrochloride (PTZ) has been shown to be active against spontaneous AKR leukemia. The long-term treatment with PTZ begining at 5–7 months of age of a group of AKR mice containing 10–20% of advanced leuke-mic mice significantly prolonged the life span of the group. The therapeutic effectiveness of PTZ has been compared with several standard antileukemic drugs. PTZ decreased the AKR virus titer in the circulating blood of mice and its antiviral activity in AKR virus infected NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Tables I-V include these results. It was confirmed that PTZ prolonged the life span of mice significantly (65 138%) over the controls, as demonstrated in our earlier experiments [3]. Among the standard cytotoxic drugs, VCR was found to be most effective, which demonstrated constantly above 100% prolongation of life span over the controls as shown in tables 1.…”
Section: Effec T O F Ptz On the Life Span O F Spontaneous Akr Leukemisupporting
confidence: 82%
See 4 more Smart Citations
“…Tables I-V include these results. It was confirmed that PTZ prolonged the life span of mice significantly (65 138%) over the controls, as demonstrated in our earlier experiments [3]. Among the standard cytotoxic drugs, VCR was found to be most effective, which demonstrated constantly above 100% prolongation of life span over the controls as shown in tables 1.…”
Section: Effec T O F Ptz On the Life Span O F Spontaneous Akr Leukemisupporting
confidence: 82%
“…Our present results demonstrated the highest activity by VCR (av erage 114% ILS), followed by PTZ (90%), MTX (71%), 6-TG (60%), and ADR (49%). Our previous results [3] showed activity of PTZ (109% ILS) and CY (139%) but no activity by BCNU. With consideration of many reports mentioned above and our results, activity of PTZ relative to standard drugs seems to be superior to those of ADR, 6-TG, and MTX and in ferior to VCR and CY.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations